Characterisation of Rice Husk and Wood Ash as Constituents for Production of Phosphorus and Potassium - Malgwi, D. J.; Jones, A. N.; Musa, M. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study investigated the potentials of rice husk and wood ashes from various species (Mahogany, Iroko and Mghelina) as sustainable sources of phosphorus (P) and potassium (K). The raw rice husk sample was obtained from Dala rice mill while different wood species such as Mahogany, Iroko and Mghelina, were obtained from Baga road timber shade both in Maiduguri, Borno State. Both raw materials were carbonized at different temperatures ranging between 350-750°C respectively. The laboratory analysis of the ash samples was conducted using atomic absorption spectrophotometer (AAS) to determine the presences of K, and P. The result shows that rice husk ash contains a mean value in terms of mg/100g of K2O (3.593) and P2O5(1.382). Also, Mahogany wood ash contains 4.48mg of K and 0.55 mg of P. Similarly, Iroko wood ash was found to consist of 5.14g of K and 0.56g of P. In addition to Mghelina wood ash(Beech wood), it was found that compounds present has a mean values in terms of g/100g of K (10.4) and P (0.96). It is noteworthy that P was highest in wood ash (mghelina) amongst the materials tested. Therefore, the presence of these compounds in wood and rice husk ashes could be a potential low-cost resource for the production of inorganic fertilizer.